2014
DOI: 10.1371/journal.pone.0107725
|View full text |Cite
|
Sign up to set email alerts
|

Human Eosinophils Express the High Affinity IgE Receptor, FcεRI, in Bullous Pemphigoid

Abstract: Bullous pemphigoid (BP) is an autoimmune blistering disease mediated by autoantibodies targeting BP180 (type XVII collagen). Patient sera and tissues typically have IgG and IgE autoantibodies and elevated eosinophil numbers. Although the pathogenicity of the IgE autoantibodies is established in BP, their contribution to the disease process is not well understood. Our aims were two-fold: 1) To establish the clinical relationships between total and BP180-specific IgE, eosinophilia and other markers of disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 60 publications
6
88
2
3
Order By: Relevance
“…Histological studies have positioned mast cell activation upstream of that of eosinophils by showing that the latter are attracted to the site of mast cell degranulation (144). Like mast cells and basophils, eosinophils were recently shown to express the high-affinity IgE receptor FcεRI, which provides an explanation of how eosinophils may be activated in BP—namely by binding anti-BP180 IgE that is crosslinked by BP180 or its degradation products (143, 145). …”
Section: Bullous Pemphigoid Pathophysiologymentioning
confidence: 99%
“…Histological studies have positioned mast cell activation upstream of that of eosinophils by showing that the latter are attracted to the site of mast cell degranulation (144). Like mast cells and basophils, eosinophils were recently shown to express the high-affinity IgE receptor FcεRI, which provides an explanation of how eosinophils may be activated in BP—namely by binding anti-BP180 IgE that is crosslinked by BP180 or its degradation products (143, 145). …”
Section: Bullous Pemphigoid Pathophysiologymentioning
confidence: 99%
“…[76] In this line, Messingham et al recently identified FcεRI on peripheral blood and skin eosinophils. [77] Tanaka et al found FcεRI expression in 70% of the eosinophils in lesional BP skin. [76] Binding of anti-BP180 NC16A IgE on these eosinophils might result in eosinophil degranulation or may trigger mast cell degranulation, which has been suggested to be in a piecemeal degranulation pattern [78,79] and therefore might contribute to blister development.…”
Section: Eosinophiliamentioning
confidence: 99%
“…The early phase of lesion development, including urticaria, eosinophil infiltration and spontaneous blistering, were only observed in models utilizing IgE autoantibodies from patient sera or monocolonal IgE antibodies specific for BP180 . Interestingly, circulating eosinophil numbers correlate with levels of both NC16A‐specific IgG and IgE in BP sera , but it is unknown if these autoantibodies directly influence lesional eosinophils.…”
Section: Introductionmentioning
confidence: 99%